2023
DOI: 10.1177/0734371x231198163
|View full text |Cite
|
Sign up to set email alerts
|

Homeworking Heaven or Hell During the COVID-19 Pandemic? Lessons for the Job Demands-Resources Model in the Context of Homeworking

Peter M. Kruyen,
Rick T. Borst,
Beatrice I. J. M. Van der Heijden
et al.

Abstract: During the COVID-19 pandemic, public servants in many countries were required to work from home. In this study, we explore Dutch public servants’ experiences of mandatory homeworking by conducting a template analysis. Based on an in-depth examination of 985 written accounts, we inductively expand an a priori template derived from the Job Demands-Resources (JD-R) framework, to understand and analyze public servants’ experiences of this new situation. We found homeworking in general had positive effects on publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Since the pandemic, several studies have explored the theoretical models of various job characteristics of WFH, like the particularly well-known Job Demands-Resources (JD-R) model (e.g., Barbieri et al, 2021;Demerouti and Bakker, 2023;Kruyen et al, 2023), which involves the linking of workplace factors strain and motivation, and the resultant organizational outcomes.…”
Section: Job Demands-resources Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the pandemic, several studies have explored the theoretical models of various job characteristics of WFH, like the particularly well-known Job Demands-Resources (JD-R) model (e.g., Barbieri et al, 2021;Demerouti and Bakker, 2023;Kruyen et al, 2023), which involves the linking of workplace factors strain and motivation, and the resultant organizational outcomes.…”
Section: Job Demands-resources Modelmentioning
confidence: 99%
“…Past research has suggested various adjustments to evaluate the applicability of the JD-R model to emerging work paradigms. For instance, Kruyen et al (2023) has expanded the model to include personal and home demands/resources in the WFH context, advocating for the clustering of individual demands and resources. In a similar vein, Barbieri et al (2021) have proposed subdividing resources into organizational and individual aspects, akin to the personal factors discussed by Kruyen et al (2023).…”
Section: Job Demands-resources Modelmentioning
confidence: 99%
See 3 more Smart Citations